Unmet Needs in Endometriosis: Lessons from COVID-19 - Niamh Waters; Louis Taffs; Jennifer L. Marino; Charlene Rapsey; Jane E. Girling; Michelle Peate (Mary Ann Liebert, 2022)
Background: One key challenge of the COVID-19 pandemic is health care access. Government-imposed restrictions and increased health care burden have induced considerable changes to health care services and their delivery. These are likely to have substantially impacted those with chronic conditions such as endometriosis, as they require sustained management. Aims: Our objective was to explore the impact of the COVID-19 pandemic on the experience of people with endometriosis, and to use this information to inform health care delivery for the management of chronic conditions in a COVID-normal future. Materials and Methods: Invitation to participate in an open-ended online survey through social media of Australian endometriosis organizations and the Royal Women's Hospital, Melbourne. Surveys were analyzed qualitatively through template analysis. Results: Of 576 surveys returned, 329 reported COVID-19 having an impact. Fifteen areas of impact were identified and grouped under three domains: impact on access to health care services, impact on daily life, and impact of isolation. Common impacts included reduced access to health care services, improved symptom management due to decreased day-to-day travel and work-from-home arrangements, and both positive and negative views of telehealth services. Conclusions: This study provides in-depth insight into the experiences of people with endometriosis during the COVID-19 pandemic, confirming previous studies' findings and offering insight into discrepancies between the Australian Healthcare system categorization of surgeries as ?non-essential,? and patient views of these procedures as ?essential? to their well-being. Results may inform future adjustments to health care services and delivery to improve the lives of people with endometriosis, and by extension, other chronic conditions.